2020
DOI: 10.1042/bsr20191370
|View full text |Cite|
|
Sign up to set email alerts
|

Protective effect of Asarum sieboldii essential oil on ovalbumin induced allergic rhinitis in rat

Abstract: Background: The study was aimed to investigate the protective effect of Asarum sieboldii Miq. essential oil (AEO) on ovalbumin (OVA)-induced allergic rhinitis (AR) in rats. Methods and results: Sixty Sprague–Dawley male rats were randomly divided into six groups (n=10): control, model, cetirizine (Cet, 4.65 g/kg), and AEO (0.5, 1.5, 3 g/kg) groups. All animals except the control group received repeated intranasal instillation with 20 μl of 20% OVA in Al(OH)3 saline solvent for 15 days. The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Traditional Chinese Medicines (TCMs) have been used for many centuries to treat multi-factorial diseases including AR. YJD is a widely used TCM regime to treat inflammatory diseases in China [ 16 , 18 , 19 , 24 ]. In this study, we confirmed that YJD alleviated OVA-induced AR in the guinea pig model by suppressing inflammation and improving cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional Chinese Medicines (TCMs) have been used for many centuries to treat multi-factorial diseases including AR. YJD is a widely used TCM regime to treat inflammatory diseases in China [ 16 , 18 , 19 , 24 ]. In this study, we confirmed that YJD alleviated OVA-induced AR in the guinea pig model by suppressing inflammation and improving cellular metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The AR model guinea pigs were established as described previously with minor modifications [ 18 , 19 ]. In brief, guinea pigs were sensitized for 15 consecutive days with intraperitoneal injections of 750 μL OVA solution, which consisted of 2 mg ovalbumin (Sigma-Aldrich, USA; cat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cell infiltration was downregulated by EOCO, and the increased eosinophil count was significantly suppressed through intranasal instillation of triamcinolone (68.6%) and EOCO (33.0% for 0.01% EOCO and 43.2% for 0.1% EOCO). Pro-inflammatory cytokines, including IL-6 and IL-8, have been known as major cytokines involved in mucus hypersecretion and AR pathogenesis [ 18 ]. Intranasal EOCO instillation suppressed mucus-producing cells in the sinonasal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…It has attracted wide attention from researchers because of its high content and strong activities. Modern pharmacological studies have demonstrated that various volatile oil ingredients in Asarum have a lot of activities such as antibacterial, treatment of allergic rhinitis, antinociceptive, anti-inflammatory, and antiallergic [5][6][7][8][9]. On the other hand, toxicological researchers found that the volatile oil ingredients in Asarum have strong phytotoxic activity and it was toxic to D. farinae adults [10,11].…”
Section: Introductionmentioning
confidence: 99%